Experimental Study on the Influences of Backlash and Elastic Deformation on the Bidirectional Operation Characteristic of Gearbox - Li Youhua; Liu Zhongming; Zhang Zhihong; Li Jiqiang; Liu Yuechan; Yu Feipeng (Jixie chuandong)
The gearbox of rack test for the Three Gorges ship lift is low speed heavy duty four stages transmission,and need frequent fast reversing operation in the process of test,due to the influence of the gear meshing backlash,elastic torsional deformation of shaft and elastic deformation of gear tooth and other factors,the operation performance of gearbox will be changed during reversing process,especially the output speed and torque. In order to analyze the influence on the transmission performance of gearbox,the calculation models of the influence of the gear meshing backlash and the elastic torsional deformation of the shaft on the rotational speed are setup respectively,the output speed of the gearbox in the reversing process is calculated and compared with the output speed of gearbox measured by experiment,which verifies the accuracy of the calculation model and the test data.